Anticancer Activity of Asiatic Acid from Centella Asiatica: A Comprehensive Systematic Review of In Vitro and In Vivo Studies - Fiki Muhammad Ridho; Panggih Fahrudin; Andika Julyanto Syachputra; Iren Angelia Aruan; Kamailiya Ulfah; Alfi Syahri (Keluwih)
Abstract—Centella asiatica, containing asiatic acid (AsA), represents one such candidate demonstrating promising anticancer effects. This study aims to comprehensively review the anticancer activity of AsA in published in vitro and in vivo studies. A systematic review method was employed and several databases, including Scopus, PubMed, ScienceDirect, and Google Scholar, were used to conduct a comprehensive and systematic search of the literature based in vitro and in vivo studies in November 2023 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Thirty-three articles were included, distributed across twenty-five in vitro studies, three in vivo studies, and five both in vitro and in vivo studies. Based on the findings in the reviewed articles, we report that AsA, a triterpene derived from C. asiatica, exhibits anticancer effects demonstrated both in various cancer cell lines and in cancer cell-induced animal model, through several mechanisms, including anti-inflammatory effects, antioxidant effects, inhibition of cell proliferation, inhibition of invasion and migration, and induction of apoptosis and autophagy. Conclusions based on findings in in vitro and in vivo studies, AsA has strong potential to be used and developed as an inhibitor of various types of cancer cells.